Монгол аман зохиолын онол судлалын тулгамдсан асуудлууд: Current issues in the Theoretical Study of Mongol Folklore - Г., Нандинбилиг (Mongolian Studies, 2023)
Considering the previous studies of Mongol folklore, numerous field researches have been done and got noticeable achievements, however there are some disadvantages of chasing after only word artistry, have left the oral and ritual researches and “cultural complex” study by dealing with the issues from the ideological point of view. In conclusion, 1. We need to appeal for researchers to re-examine the previous studies which were only focused on literary artistry and ignored the authentic and pseudo characteristics of folklore, its oral and ritual tradition. 2. Further studies on folklore need to be examined the oral characteristics, manner, ritual and symbolic characters and characteristic of art of words in complex way. So that, basic principles remind us to depend on the original context of source material at both levels of collecting and compiling source materials and theoretical analysis.